DEVELOPMENT OF ANDROID-BASED COLLABORATIVE MEDIA FOR EARLY CHILDREN AT POS PAUD ASTER 36 KEBONAGUNG KALIWATES JEMBER - Muzaiyanah Muzaiyanah; Nurul Anam; Umah Amrela (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
This research is motivated by problems regarding teachers in conveying learning material that is still conventional. In addition, there is a lack of variations in learning media, so that in the learning process children are sometimes diverted from other activities, in the process of delivering material, the teacher only focuses on the question and answer method. Thus, the purpose of this study was to find out the development of android-based collaborative media for early childhood at the Aster 36 Kebonagung Kaliwates Jember Academic Year 2021/2022. This research method uses R&D and the development model uses the ADDIE Model. Methods of data collection using questionnaires, observation, interviews, and documentation. Analysis of the data using statistical analysis and Miles & Huberman. The results of this research indicate that the development stage of collaborative media based on android for early childhood at Pos PAUD Aster 36 Kebonagung Kaliwates includes the process of analyzing the characteristics of students; determine KD (Basic Competence); choosing media, teaching materials and methods; designing and using media and learning materials in android-based media; involve students in the learning process using android-based media; and evaluate and revise Android-based media products.